2019
DOI: 10.1002/jmv.25539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of human adenoviruses in hospitalized children <5 years old with acute gastroenteritis in Tehran, Iran

Abstract: Human adenoviruses (HAdVs), especially AdV-40 and 41, are common causes of nonbacterial sporadic and outbreak gastroenteritis in children. The present study aimed to describe the frequency and genetic analysis of HAdVs in hospitalized children <5 years old with acute gastroenteritis. A total of 376 stool samples obtained from June 2015 to December 2017 were investigated for the presence of HAdVs by polymerase chain reaction. The HAdV DNA was detected in 16 (4.3%) out of 376 stool samples. Based on the hexon hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…This AdV41 had been reported from children acute gastroenteritis in previous studies of India, Thailand, Iraq, and many other countries. AdV5, AdV7, and AdV8 had also been reported from nearby countries of Bangladesh 1,36,37 . Our study found AdV41 was the most prevalent in children stool samples which is in agreement with previous studies of India, Thailand, and Iraq 38,39 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This AdV41 had been reported from children acute gastroenteritis in previous studies of India, Thailand, Iraq, and many other countries. AdV5, AdV7, and AdV8 had also been reported from nearby countries of Bangladesh 1,36,37 . Our study found AdV41 was the most prevalent in children stool samples which is in agreement with previous studies of India, Thailand, and Iraq 38,39 …”
Section: Discussionsupporting
confidence: 92%
“…AdV5, AdV7, and AdV8 had also been reported from nearby countries of Bangladesh. 1,36,37 Our study found AdV41 was the most prevalent in children stool samples which is in agreement with previous studies of India, Thailand, and Iraq. 38,39 In this study, most of the infants and children with AdV infection (64%) were aged less than 24 months.…”
Section: Discussionsupporting
confidence: 92%
“…Infectious agents, particularly viruses are the main cause of GE worldwide ( 2 ). Before the implication of Rotavirus vaccination, Rotavirus was the leading cause of viral GE, while other enteric viruses, such as Noroviruses, Astroviruses, and Human adenoviruses, are now the most prevalent viruses causing GE ( 3 ). Besides the aforementioned enteric viruses, the list of enteric viruses is continuously growing due to the discovery of emerging viruses ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Species F is primarily associated with gastroenteric disorders. Initial epidemiological studies on the prevalence of HAdV-40 and HAdV-41 reported that the occurrence rates of these genotypes were approximately equal [51]. However, the pattern of occurrence of these genotypes has changed in recent years, with a reduction in HAdV-40 and an increase of HAdV-41.…”
Section: Discussionmentioning
confidence: 99%